Approximate Fixed Point Theorems in Fuzzy Norm Spaces for an Operator. (30th April 2013) - Mohsenalhosseini, S. A. M.; Mazaheri, H.
Abstract : We define approximate fixed point and fuzzy diameter in fuzzy norm spaces. We prove theorems for various types of well-known generalized contractions on fuzzy norm spaces with the use of two general lemmas that are given regarding approximate fixed points of operators on fuzzy norm spaces.